Seminar and Workshop on Object Recognition using Deep Learning at Sam Ratulangi University Manado - Dewi, Christine (Jurnal Pengabdian Masyarakat, 2024)
Purpose: This seminar and workshop aim to address the lack of understanding among students regarding object recognition with deep learning. By exploring the concepts and applications of deep learning in object detection and recognition, participants will gain insights into this crucial aspect of computer vision. Method: The event will feature lectures, practical demonstrations, and hands-on workshops conducted by experts in the field. Participants will engage in interactive sessions to deepen their understanding of convolutional neural networks and other deep learning techniques for object recognition. Practical Applications: The knowledge gained from this seminar and workshop will have practical implications across various industries, including autonomous vehicles, healthcare, security systems, and robotics. Participants will learn how to apply deep learning algorithms to solve real-world problems related to object detection and recognition. Conclusion: By the end of the seminar and workshop, participants are expected to have acquired a deeper understanding of object recognition with deep learning and its practical applications. This will contribute to bridging the gap between theoretical knowledge and real-world implementation in the field of computer vision.